ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING PADA PT. DAN LIRIS DI SUKOHARJO - Permadani, Septiana Bunga; Widajanti, Erni; Sunarso, Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
The purpose of this research is to analyze the efficiency of raw material inventory control system PT. Dan Liris as well as analyzing the application of material requirement planning method in optimizing inventory control raw materials in PT. Dan Liris. This research is a case study on PT. Dan Liris. The data type used is qualitative data and quantitative data. The data source in research using secondary data. Methods of data collection were used: interviews, observation and documentation. Technique of data analysis using the techniques of Material Requirements Planning (MRP). Based on the results of research: the raw material needs planning Policy implemented by the PT. Dan Liris yet structured, it is apparent from the raw material procurement system which uses a method of forecasting in accordance with sales targets. Application of the method of Material Requirements Planning can play a role in optimize raw material inventory control PT. Dan Liris, it is shown in the total cost of the inventory using the technique of Lot For Lot is Rp 40.2 million, total the cost of inventories using the techniques of Economic Order Quantity amounting to Rp 44,541,085 and the total cost of the inventory using the policy of the company amounting to Rp 119,548,146. From the comparison it can be noted that a very effective technique to achieve cost-efficiency the total inventory of raw materials is the technique of Lot For Lot.